Make your business grow : take a strategic approach - Irwin, David (London : International Thomson Business Press, 1998)
The importance of strategic thinking. Looking out. Looking ahead. Looking inwards. Defining a direction. Defining objecttives and measuring performance. Managing for success. Strategy checklist to help your business grow.
Keywords: Business; Strategic planning; Strategic planning -- Case studies; Business enterprises -- Case studies